Relating fractographic analysis to yield strength of novel X7475 (Al–Zn–Mg–Cu) alloys produced by recycling aluminium beverage cans - Kazeem, Abubakar; Badarulzaman, Nur Azam; Wan Ali, Wan Fahmin Faiz (Elsevier, 2020)
The aim of this letter was to conduct a postmortem on the nature of fracture, substrates and possible precipitates formed in a novel experimental 7xxx alloy cast from recycled beverage cans (RBCs) and link same to yield strength (ry) following heat treatment (HT). Fractographic investigation revealed the formation of dendrites and hardening phases such as MgZn2 and Al2Mg3Zn3 among others, following HT. An alloy S10 recorded the peak ry of 117.200 MPa while S3 was the least with 51.212 MPa and extension (e) of 0.197 mm.